(untitled) (Jurnal Pembangunan Perikanan dan Agribisnis, 2017)
This research aims to determine the costs, benefits, based on economic performance Revenue Cost Ratio (RCR), Break Even Point (BEP), Pay Back Period and marketing channel operating results processing on the Salted Fish Business (Channa striata) in the village of Salimbatu, Central Tanjung Palas Subdistrict, Bulungan District, North Kalimantan Province. The method used in this research is survey method. The data collected is secondary data retrieval is done by census samples whose methods census conducted interviews with four respondents that have salted fish business. The results showed that the with an average profit of Rp. 3,184,304, - each month, for the calculation of Revenue Cost Ratio in salted fish business (Channa striata) in the village of Salimbatu amounted to 1.4 which means that this business generated a profit of 1.4 times of the total costs incurred. Exceeds the balance point salted fish business (Channa striata), both in terms of production, sales and pricing breakeven or in other words the business is profitable. Then for Payback Period of return of investment cost is for 3,8 years, it means less than 7 years of investment business is feasible to be continued and the processing and marketing channels fish business (Channa striata) in the village of Salimbatu is known to use marketing channels to zero level and two levels.